Public Perception of Baznas Services in Cilegon Banten City - Ubaidillah, Taufiq; Bahri, Syaeful; Syarifuddin, Efi (Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study was motivated by the community's habit of paying zakat through BAZNAS Cilegon City. Even though the population of this village is predominantly Muslim and the income of the people is very high, this is just unfulfilled potential. Apart from that, this great potential must be supported by excellent service from the Cilegon City Baznas to maximize this great potential. This research aims to find out how the public perceives BAZNAS services in Cilegon City. This research uses a quantitative approach with a survey method to generalize the population from several samples so that conclusions can be made. The data sources for this research are informants from several communities as a result of the informants. Furthermore, the data collection technique in this research uses a questionnaire distributed to the public. Then the results are analyzed descriptively (descriptive analysis) and then the results are interpreted through survey results in the form of tables or images. The results of research on the analysis of the level of conformity between the level of perception and preferences of Muslim tourists towards Cilegon City Baznas services show that the average level of conformity is 100%, which means very good. However, several aspects must be a priority in improving services to the community, namely the human resources aspect with the attribute "Responsive officers in responding to community needs" and the aspect of ease of information and speed of service with the attribute.